Foreign language reading anxiety and its correlates: a meta-analysis - Li, Rui (Reading & writing, 2022)
Despite the growing body of research on foreign language reading anxiety, there is still a dearth of comprehensive meta-analysis regarding the effect sizes of these studies. To fill the gap, this study meta-analyzed the overall average correlation between foreign language reading anxiety and its correlates among 9785 participants: two high-evidence correlates (language anxiety and reading performance with 18 to 27 aggregated effect sizes) and two low-evidence correlates (with less than nine aggregated effect sizes: reading self-efficacy and reading strategy). In addition, moderator analyses of target language, age, foreign language proficiency, language distance and test type were also carried out for the high-evidence correlates. The results obtained a moderate correlation of language anxiety and reading performance. The two low-evidence correlates had moderate-to-large and moderate effect sizes, with reading self-efficacy being moderate-to-large and reading strategy being moderate. Foreign language proficiency and age were significant moderators for some correlations. Implications of the findings were discussed.